Toll-like receptors 2 and 4, and bacterial proteins in IgG4-related sialadenitis, other types of chronic sialadenitis and sialolithiasis - Waltimo, Elin; Eray, Mine; Mäkitie, Antti; Haglund, Caj; Atula, Timo; Hagström, Jaana (Taylor & Francis, 2025)
Background: The association of chronic sclerosing sialadenitis and IgG4-related disease (IgG4-RD) has resulted in the more frequent identification of IgG4-positivity in submandibular gland inflammations, also uncovering IgG4 overexpression in nonspecific inflammations. These findings lead us to hypothesise that IgG4-positive sialadenitis represents a continuous inflammatory process overlapping histologically with IgG4-RD, possibly differing in aetiology. However, the antigen underlying IgG4 overexpression in IgG4-positive sialadenitis and IgG4-RD remains unknown.
Materials and methods: Here, we investigated toll-like receptor (TLR) - mediated bacterial inflammation in submandibular gland tissues of patients with IgG4-positive and IgG4-negative chronic inflammatory lesions of the submandibular gland (n = 61), with noninflamed submandibular glands serving as controls (n = 4). Utilising immunohistochemistry, we assessed the expression of TLR2 and TLR4, lipopolysaccharide (LPS) and the P. gingivalis-specific antigen gingipain R1.
Results: We observed TLR2- and TLR4-immunopositivity in 64 (98%) samples. However, TLR2 and TLR4 staining intensity was significantly stronger in the IgG4-positive group. LPS- and gingipain R1 immunopositivity were observed in 56 (86%) and 58 (89%) samples, respectively. LPS-positivity localised exclusively in mast cell-like cells, while gingipain R1-positivity remained scarce.
Conclusions: A stronger TLR2 or TLR4 expression in IgG4-positive sialadenitis may indicate a tissue-related factor underlying this form of chronic sialadenitis. LPS- and P. gingivalis immunopositivity remained weak throughout this series. Thus, gram-negative bacteria may not represent pathogens underlying these forms of chronic sialadenitis.